Optimizing Prophetic Life Skills in Islamic Boarding Schools: Evidence in Indonesia - Achmad Lutfi Affandi; Dhiya Atul Millah (CV. Gerasi Insan Nusantara, 2026)
Pesantren has great potential in shaping character and equipping students with relevant life skills through the Prophetic Life Skill approach, which is the integration of spiritual values, morals, and practical skills based on prophetic teachings. This research aims to explore the strategy of implementing Prophetic Life Skills at Pesantren Rahmatan Lil 'Alamin Patianrowo Nganjuk and the challenges faced. This pesantren is interesting because it is able to survive and develop in the midst of limited funds, infrastructure, and the majority of students from the poor, through cadre programs and innovative business units. The research used a qualitative approach with a case study method. The results showed that the pesantren successfully implemented the four main dimensions of Prophetic Life Skills: (1) independence, through involving santri in productive activities and business management; (2) entrepreneurship, based on local potential with an Islamic work ethic; (3) leadership, through regeneration and santri organizations; and (4) communication and collaboration through social training and da'wah. This application forms santri who are religious, productive, and ready to face the challenges of the times. This model shows high relevance to Islamic values and can be an alternative to sustainable pesantren education in human resource development.